Antibiotic action of seed lipids from five tree species grown in Turkey - Digrak, M; Bagci, E; Alma, MH (Swets Zeitlinger Publishers, 2002)
In this study, the seed lipids of Austrian pine (Pinus nigra Arnold.), Ehrami pine (Pinus nigra var. pyramidalis), Caucasian fir [Abies nordmanniana (Stev.) Spach], Eastern red (Thuja orientalis L.) and Scots pine (Pinus sylvestris L.) grown in Turkey were extracted with a mixture of methanol and chloroform. The bacterial and antifungal activities of the seed lipids were tested against various pathogenic bacteria and fungi by applying the disc-diffusion method. The seed lipids of A. nordmanniana were found to be most effective against the tested microorganisms, except for Pseudomonas aeruginosa and Micrococcus luteus bacteria, followed by T. orientalis and P. sylvestris, respectively. However, the seed lipids of P. nigra var. pyramidalis were not effective on the growth of any microorganism. Bacillus subtilis and Listeria monocytogenes bacteria were found as the most resistant bacteria in the study. Furthermore, the seed lipids of A. nordmanniana and, somewhat, T. orientalis, were generally comparable to two reference antibiotics.
Keywords: seed lipids; antifungal activity; antibacterial activity; tree species; Turkey; disc-diffusion method